Aplikasi Ekstrak Pestisida Nabati Terhadap Hama Walang Sangit (Leptocorisa oratorius) Pada Tanaman Padi Varietas Ciherang - Lia Kristiana; Rina Hardiyati (Universitas Islam Madura, 2022)
The formulation of the research problem is how the effect of the application of vegetable pesticide extract against walang sangit(Leptocorisa oratorius) on Ciherang variety rice plants. The purpose of this study was to determine the effect of application of vegetable pesticide extract on walang sangitpest (Leptocorisa oratorius) on ciherang variety rice plants. The type of research conducted was an experimental completely randomized design pattern (CRD) of 5 treatments and 4 replications. The treatments used were P0 = 0 ml, P1 = 200 ml, P2 = 300 ml, P3 = 400 ml, P4 = 500 ml. tabulated data was then analyzed using Variant Analysis (ANAVA). The results of this study showed that there was no effect of the application of vegetable pesticide extract on the number of stems in each clump and the number of grains attacked, but significantly affected the number of dead walang sangit bug and the number of grains not attacked with the most effective concentration indicated by a concentration of 400 ml, and Attack Intensity (IS) is still in the light category. It can be concluded that the application of plant-based pesticide extract has a very real effect on the grain not attacked with the most effective concentration is 400 ml with an average number of 275.75.The higher the concentration of vegetable pesticide extract, the higher the death rate in walang sangit pest(Leptocorisa oratorius). So that the effect on the number of grains is not attacked. Keywords: Vegetable Pesticides, Walang Sangit, Rice